Substantia nigra pars reticulata units in 6-hydroxydopamine-lesioned rats: Responses to striatal D2 dopamine receptor stimulation and subthalamic lesions - Tseng, Kuei y (2000)
In order to increase our understanding of Parkinson's disease pathophysiology, we studied the effects of intrastriatally administered selective dopamine receptor agonists on single units from the substantia nigra pars reticulata of 6-hydroxydopamine (6-OHDA)-lesioned rats with or without an additional subthalamic nucleus lesion. Nigral pars reticulata units of 6-OHDA-lesioned rats were classified into two types, showing regular and bursting discharge patterns, respectively ('non-burst' and 'burst' units). Non-burst and burst units showed distinct responses to intrastriatal quinpirole (the former were excited and burst units inhibited). Furthermore, subthalamic nucleus lesions significantly decreased the number of nigral units showing a spontaneous bursting pattern, and reduced the proportion of units that responded to quinpirole. In contrast, subthalamic lesions did not alter the proportion of nigral units that responded to SKF38393, although the lesions changed some response features, e.g. response type and magnitude. Burst analysis showed that quinpirole did not modify the discharge pattern of burst units, whereas SKF38393 produced a shift to regular firing in 62 of the burst units tested. In conjunction, our results support that: (i) the subthalamic nucleus has an important influence on output nuclei firing pattern; (ii) striatal D2 receptors have a strong influence on nigral firing rate, and a less relevant role in controlling firing pattern; (iii) burst and non-burst units differ in their response to selective stimulation of striatal dopamine receptors; (iv) the effects of striatal D2 receptors on nigral units are mainly, though not exclusively, mediated by the subthalamic nucleus; and (v) nigral responses to SKF38393 involve the subthalamic nucleus.